An evaluation of mindfulness-based childbirth and parenting courses for pregnant women and prospective fathers/partners within the UK NHS (MBCP-4-NHS). (September 2018) - Warriner, Sian; Crane, Catherine; Dymond, Maret; Krusche, Adele
Highlights: Mindfulness meditation successfully combined with antenatal education in the NHS. Brief (MBCP-4-NHS) antenatal mindfulness course may improve parental mental health. Large scale longitudinal RCT is justified/needed to further investigate MBCP-4-NHS. RCT could explore health and economical costs/benefits to parents and infants. Abstract: An evaluation of mindfulness-based childbirth and parenting courses for pregnant women and prospective fathers/partners within the UK NHS (MBCP-4-NHS). Objective : To explore the usefulness within the National Health Service (NHS) of a brief (four week, ten hour) course based upon the Mindfulness Based Childbirth and Parenting (MBCP) programme (Duncan and Bardacke, 2010 ) described here as MBCP-4-NHS. Background : The National Maternity Review (2016) and report of The Independent Mental Health Taskforce to theNHS (2016a, 2016b ) in England highlight the need for significant investment into perinatal mental health services, with the Government pledging funding to improve such services through a range of measures. Whilst the field of mindfulness during the perinatal period is in need of well controlled trials and studies exploring the mechanisms of action (Hall et al., 2016 ) the limited research to date supports the potential for mindfulness based interventions in pregnancy and the need for further scientific study in this area (Dhillon et al., 2017; Shi and Macbeth, 2017). Particularly because it may broaden women's repertoire of coping strategies with the potential to improve the developmental trajectory of both parents and infants (Dunn et al., 2012 ;Duncan and Bardacke, 2010 ;Vieten and Astin, 2008 ). However, most of the studies to date have involved lengthy courses of around 8–9 weeks (24 h) duration, which may not be feasible or economical within a UK NHS setting and therefore, would be unlikely to be adopted as routine practice. Design : An initial pilot study to discover if MBCP-4-NHS is acceptable and feasible within NHS maternity services, comparing maternal and paternal pre and post intervention self-report measures of mental health to begin to explore the effectiveness of this intervention. Setting : NHS antenatal education classes held in children's centres for expectant parents across Oxfordshire. Participants : All expectant parents receiving Oxfordshire maternity services between October 2014 and January 2015 were invited to self-refer into the intervention, of which 155 individuals (86 women and 69 men) took part. Intervention : 'MBCP-4-NHS' – A brief (four week, ten hour) course developed from the nine week Mindfulness Based Childbirth and Parenting (MBCP) intervention. Measures : Self-report measures of mental health including low mood/depression, mindfulness, stress, anxiety, pregnancy related distress and experiences. Findings : The results showed a significant increase in both maternal and paternal mental health with women demonstrating a significant improvement in symptoms of stress, anxiety, depression, pregnancy-related distress, labour worry and positive and negative pregnancy experiences; and men improving significantly in symptoms of anxiety, depression and showing a trend for improvement in self-reported symptoms of perceived stress. Conclusions : This is a promising antenatal intervention that can be feasibly implemented within NHS which might have the potential to impact upon parental mental health and, therefore, possibly also the health of next generation. However, caution is needed interpreting these findings given that this study did not include an active control group. Implications for practice : This research provides a clear rationale and justification for a large randomised control trial of this intervention within the NHS, which should include a more diverse population, across multiple centres and should explore both the potential health benefits for parents and infants/children as well as potential economic costs/benefits.